Relationship of Clinical Picture, Phenotype of Oxidative Metabolism, Accentuation of Temperament Properties and Compliance in Patients with Gastroesophageal Reflux Disease - A. A. Kalugin; A. A. Stepchenko; M. A. Stepchenko (SINAPS LLC, 2022)
The purpose of the study is to establish the relationship between the accentuation of temperament properties, clinical picture of disease, and adherence to therapy in patients with gastroesophageal reflux disease with different phenotype of oxidative metabolism. Materials and methods. To achieve this goal, a case-control study was conducted in 156 patients aged 21 to 55 years (101 men and 55 women, mean age 38 years (IQR 29-46)) with verified gastroesophageal reflux disease with assessment of the clinical picture, assessment of the severity of symptoms using a visual analogue scale, concomitant pathology, adherence to therapy, phenotype of oxidative metabolism with the eufillin marker drug, determination of personal psychophysiological features using a temperament accentuation test. Statistical analyses were performed according to study objectives and data set features. Results. In patients with gastroesophageal reflux disease, 3 main personality types were identified: hyperthymic (n = 29; 19 %), mixed (n = 61; 39 %) and emotionally unstable type (n = 66; 42 %). By oxidative metabolism phenotype, 156 patients were divided into rapid (n = 51; 33 %), intermediate (n = 82; 52 %) and slow metabolizers (n = 23; 15 %). Analysis of multinomial logistic regression showed that in patients with rapid metabolism, in contrast to intermediate and slow metabolizers, low pain syndrome intensity should be expected (p = 0.014). There was no effect on the clinical presentation of temperament properties (p = 0.063). When studying the dependence of adherence to therapy on the properties of temperament and the patient`s metabolic level by multinomial logistic regression in patients with a hyperthymic type of accentuation of temperament properties, the probability of high adherence to therapy was more than 65 % in fast and intermediate metabolizers and 100 % in slow metabolizers (p = 0.006), in patients with mixed types the probability of high adherence to therapy is observed only in slow metabolizers (p = 0.006), patients with emotionally unstable type have a high probability of low adherence to therapy regardless of metabolic level (p = 0.006). Conclusion. To predict adherence of patients with gastroesophageal reflux disease to therapy, it is advisable to determine the level of oxidative metabolism and the type of accentuation of temperament properties.